Analysis of Strategic Agility and Digital Transformation on Innovation Capability and Competitive Advantage in Technology Startups in Bandung - Fitriani, Heny; Mayratih, Siska; Erdawati, Lena; Sudarmanto, Eko (West Science Journal Economic and Entrepreneurship, 2026)
This study examines the effects of strategic agility and digital transformation on innovation capability and competitive advantage among technology startups in Bandung, Indonesia. A quantitative research design was employed using a cross-sectional survey involving 190 respondents who were directly engaged in technology startup activities. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed through Partial Least Squares Structural Equation Modeling using SmartPLS 3. The findings show that strategic agility has a positive and significant effect on innovation capability and competitive advantage. Digital transformation also has a positive and significant effect on innovation capability and competitive advantage. Innovation capability has a strong positive and significant effect on competitive advantage. Furthermore, innovation capability significantly mediates the relationships between strategic agility and competitive advantage and between digital transformation and competitive advantage. The model explains 68.4% of the variance in innovation capability and 75.6% of the variance in competitive advantage. These findings indicate that technology startups can strengthen their competitive position by combining strategic responsiveness, digital integration, and continuous innovation. The study contributes to the Resource-Based View and Dynamic Capabilities perspective by demonstrating that innovation capability functions as a key mechanism through which strategic agility and digital transformation generate competitive value.
Keywords: Competitive Advantage; Digital Transformation; Innovation Capability; Strategic Agility; Technology Startups